Stereological Examination of Curcumin’s Effects on Hippocampal Damage Caused by the Anti-Epileptic Drugs Phenobarbital and Valproic Acid in the Developing Rat Brain - Demirel Yılmaz, B.; Eren, B.; Sagir, D.; Eren, Zerrin; Başardı Gökçe, A. (Elsevier GmbH, 2019)
The anti-epileptic drugs phenobarbital and valproic acid have an extremely strong negative effect on cognitive processes such as learning and memory in the developing brain. We examined whether or not curcumin has protective effects on neuronal injury caused by these drugs in the developing rat brain. Young male Wistar rats were studied in two groups, a 7 days old and a 14 days old group (35 rats in each). Both groups were then divided into 7 sub-groups as the control, curcumin, dimethylsulfoxide, phenobarbital, valproic acid, phenobarbital + curcumin, and valproic acid + curcumin groups (n = 5 in each group). At 24 h after the intraperitoneal injection of the compounds, the rats were sacrificed, and the hippocampal tissue was subjected to stereological analysis with the optical fractionation method. Total numbers of neurons in the hippocampus of the 7 days old and 14 days old rats were calculated. It was found that treatment with phenobarbital resulted in a loss of 43% of the neurons, and valproic acid induced a loss of 57% of the neurons in the 7 days old rats. Curcumin prevented this loss significantly with only 19% in the phenobarbital group and 41% in the valproic acid group. In the 14 days old rat groups, phenobarbital was found to reduce the number of neurons by 30%, and valproic acid reduced it by 38%. Curcumin treatment limited neuronal loss to 3% in the phenobarbital + curcumin group and 10% in the valproic acid + curcumin group. These data strongly indicate that curcumin is a protective agent and prevents hippocampal neuronal damage induced by phenobarbital and valproic acid treatment. © 2019 Elsevier GmbH
Keywords: Curcumin; Hippocampus; Phenobarbital; Stereology; Valproic Acid